An Investigation into the Human Element of On‐farm Animal Welfare Incidents in Ireland. Issue 4 (20th November 2014) - Devitt, Catherine; Kelly, Patricia; Blake, Martin; Hanlon, Alison; More, Simon J.
Abstract: A previous study on key farm performance indicators for animal welfare incidents in Ireland provided anecdotal evidence to suggest that farm animal welfare standards are often underpinned by social and human health‐related factors among farmers. The present study took an exploratory approach to identify these factors and how they influence farm animal neglect. Semi‐structured interviews were conducted with farmers. Identified factors included farming difficulties associated with age and help on the farm ( n = 5), mental health‐related problems ( n = 4), and differing perceptions of animal welfare ( n = 4). Stress was a prevalent theme. Evidence suggests that these negative human factors impact on farmers' ability to carry out farm management activities. Poor uptake of support services was noted and barriers included resistance, self‐reliance and an inability to talk openly about mental health problems. Initiatives such as the early warning system, aimed at reducing the incidence of farm animal neglect in Ireland, should be understood as often involving a human element. In particular, further research is required into how mental health problems may lead to altered or reduced regard for animal welfare.